2013
DOI: 10.1590/s0100-06832013000400007
|View full text |Cite
|
Sign up to set email alerts
|

Pedotransfer functions to estimate retention and availability of water in soils of the state of Santa Catarina, Brazil

Abstract: SUMMARYStudies on water retention and availability are scarce for subtropical or humid temperate climate regions of the southern hemisphere. The aims of this study were to evaluate the relations of the soil physical, chemical, and mineralogical properties with water retention and availability for the generation and validation of continuous point pedotransfer functions (PTFs) for soils of the State of Santa Catarina (SC) in the South of Brazil. Horizons of 44 profiles were sampled in areas under different cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 36 publications
1
25
0
12
Order By: Relevance
“…The structural data showed that the highest diversities (H') of cacti were in A2 and A4, which had a mean annual rainfall of less than 650 mm and higher percentages of fine soil particles (clay and silt), which supposedly allows for a greater water-retention capacity than do other soil particle sizes (Nobel 2003;Gurevich et al 2009). More studies are needed to infer about the relationship between granulometry and water retention in Brazilian soils, but some studies have found a tendency for soils with a greater proportion of fine particles to possess a greater capacity for water retention (Oliveira et al 2002;Costa et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The structural data showed that the highest diversities (H') of cacti were in A2 and A4, which had a mean annual rainfall of less than 650 mm and higher percentages of fine soil particles (clay and silt), which supposedly allows for a greater water-retention capacity than do other soil particle sizes (Nobel 2003;Gurevich et al 2009). More studies are needed to infer about the relationship between granulometry and water retention in Brazilian soils, but some studies have found a tendency for soils with a greater proportion of fine particles to possess a greater capacity for water retention (Oliveira et al 2002;Costa et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Soybean producing areas may be adversely affected after years of stress from either lack or excess of water because both retention and availability of water can affect plant growth and yield (Costa et al, 2013) by affecting water uptake by plants (Carlesso, 1995). The study of management practices that improve hydro-physical properties of the soil becomes essential to optimize soybean cultivation in such areas.…”
Section: Introductionmentioning
confidence: 99%
“…Os solos do Litoral Sul são formados por sedimentos recentes de rochas sedimentares, nos quais são encontrados altos teores de areia, que possivelmente não apresentam minerais que contenham As, além da baixíssima capacidade de adsorção química desse material. Outra questão é que os solos do Litoral Sul se encontram em relevo plano e são bem drenados (Costa et al, 2013), o que permite uma maior lixiviação dos elementos presentes nos mesmos.…”
Section: Resultsunclassified
“…Seasonal variations were observed with higher turbidity, DO, and N-products during the rainy season ( Figure 2a). Rises in turbidity depending on the basin drainage area and water flow are commonly documented and related to sediment re-suspension in the water column (Costa et al, 2013). This process also causes water aeration and a consequent increase in DO.…”
Section: Water Qualitymentioning
confidence: 99%